A conciliatory and persuasive social campaign changes owner behavior to reduce cats' hunting - Edith MacDonald; Mark Farnworth; Yolanda vanHeezik; Kevin Stafford; Wayne Linklater (Conservation Science and Practice, 2024)
Abstract Solutions to the cats‐hunting‐wildlife environmental conflict could benefit from social science approaches. Our Theory of Planned Behavior questionnaire—informed by an elicitation survey of cat owners at veterinary clinics about their attitudes, norms, and beliefs regarding bringing their cats inside at night—surveyed 158 cat owners across 20 veterinarian clinics in four cities. It revealed that wildlife conservation was not influential on cat owner intention but veterinarians, cat safety, peers, and household members were. Thus, we designed a social marketing campaign with two treatments: (1) a veterinarian/cat safety message or (2) social/family norm message. Thirty‐four veterinary clinics received one of the two campaign posters or served as the control group. Customers (n = 510) received a “cat welfare” survey and then a pamphlet with the advocated message, and a follow‐up survey by email or telephone 3–6 weeks later (69% response rate). Campaign messaging significantly increased the number of cat owners who reported bringing their cats inside at night compared to the control group. The social/family norm message was most effective. Although rudimentary, the campaign generated measurable changes in cat owner intention and behavior. Conservation campaigns informed by co‐benefits for cat owners may reduce cats' hunting and be conciliatory ways of transcending environmental conflict.